2014
DOI: 10.1002/aic.14504
|View full text |Cite
|
Sign up to set email alerts
|

Global optimization for sustainable design and synthesis of algae processing network for CO2 mitigation and biofuel production using life cycle optimization

Abstract: Global optimization for sustainable design and synthesis of a large-scale algae processing network under economic and environmental criteria is addressed. An algae processing network superstructure including 7800 processing routes is proposed. Based on the superstructure, a multiobjective mixed-integer nonlinear programming (MINLP) model is developed to simultaneously optimize the unit cost and the unit global warming potential (GWP). To efficiently solve the nonconvex MINLP model with separable concave terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
107
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 56 publications
0
107
0
Order By: Relevance
“…20 Pokoo-Aikins et al concluded algal biodiesel is competitive with food-based plant oil. 21 Additionally, much effort was also made on sustainable design and synthesis of thermochemical conversion system, [22][23][24][25][26][27] offering useful ideas for the integration of energy systems. Even with the above progress, there still lacks 4…”
Section: Introductionmentioning
confidence: 99%
“…20 Pokoo-Aikins et al concluded algal biodiesel is competitive with food-based plant oil. 21 Additionally, much effort was also made on sustainable design and synthesis of thermochemical conversion system, [22][23][24][25][26][27] offering useful ideas for the integration of energy systems. Even with the above progress, there still lacks 4…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the aforementioned methods, multi-objective optimization schemes have a higher potential to obtain the optimal trade-off between conflicting economic and environmental objectives. For example, a global optimization method for sustainable design was developed, in which a large-scale algae processing network was simultaneously optimized in terms of minimizing the unit cost-and global warming potential-associated indicators [9]. Additionally, a multi-objective genetic algorithm was used to solve a single objective mixed integer nonlinear programming problem related to environmental impacts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers and engineers have contributed in an effort to develop systematic methodologies for sustainable process design, online/offline optimal search for sustainable operating conditions, as well as control strategies with the ability of improving the sustainability performance of chemical processes. In the last two decades, several emerging fields have been proposed in the area of sustainable design and optimization, such as process integration [4], process intensification [5], multi-objective optimization [6][7][8][9] and real-time operation along with sustainable corporate-scale management [10,11]. One common way to incorporate sustainability indicators (environmental and social aspects) into process design and optimization is to treat such indicators as constraints in the problem objective of maximizing profitability or minimizing the cost of the operations.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we first apply the parametric algorithm based on the exact Newton's method to circumvent the computational challenge resulting from the fractional objective function. [47][48][49] As a result, a parameter uc is introduced to replace the fractional objective function with a linear parametric function, and the original SMILFP problem is transformed to a set of stochastic mixed-integer linear programming (SMILP) subproblems targeting on finding the optimal value of uc. To further improve the computational efficiency, the resulting two-stage SMILP subproblem is solved using the L-shaped method.…”
Section: A Novel Optimization Algorithmmentioning
confidence: 99%